Floral Color, Anthocyanin Synthesis Gene Expression and Control in Cape Erica Species - Le Maitre, N C; Pirie, Michael David; Bellstedt, Dirk U. (Frontiers in Plant Science, 2019)
The Cape Floristic Region (CFR) is a biodiversity hotspot, recognised globally for its unusually high levels of endemism. The origins of this biodiversity are a long-standing topic of research. The largest “Cape clade”, Erica, radiated dramatically in the CFR, its ca. 690 species arising within 10-15 Ma. Notable between- and within-species flower colour variation in Erica may have contributed to the origins of species diversity through its impact on pollinator efficiency and specificity. We investigate the expression and function of the genes of the anthocyanin biosynthesis pathway that controls floral colour in 12 Erica species groups using RT-qPCR and UPLC-MS/MS. Shifts from plesiomorphic pink- or red- to white- and/or yellow flowers were associated with independent losses of single pathway gene expression, abrogation of the entire pathway due to loss of the expression of a transcription factor or loss of function mutations in pathway genes. Striking floral colour shifts are prevalent amongst the numerous species of Cape Erica. These results show independent origins of a palette of mutations leading to such shifts, revealing the diverse genetic basis for potentially rapid evolution of a speciation-relevant trait.